Impact of donor age on recipient morbidity and mortality after living donor liver transplantation. Issue 7 (2nd July 2022) - Yeow, Marcus; Pang, Ning Qi; Muthiah, Mark D.; Soon, Gwyneth; Yock‐Young, Dan; Bonney, Glenn Kunnath; Iyer, Shridhar Ganpathi; Madhavan, Krishnakumar; Kow, Wei Chieh Alfred
Abstract: Background: Evidence for use of graft from older donors in living donor liver transplantation (LDLT) has been conflicting. This study aims to clarify the impact of donor age on recipient morbidity and mortality after adult LDLT. Methods: A total of 90 live liver donors and recipients who underwent primary adult‐to‐adult LDLT were divided into three groups according to donor age: donors in 20s (D—20s) group, donors in 30s and 40s (D—30s and 40s) group and donors in 50s & 60s (D—50s and 60s) group. Multivariate analyses were conducted to look for independent risk/prognostic factors. Donor age was analysed as a continuous variable to determine an optimal cut off. Results: Overall donor morbidity was 4/90 (4.44%), major donor morbidity was 1/90 (1.11%) and there was no donor mortality. Recipients in the D—20s group had better 1‐, 3‐ and 5‐year recipient survival than recipients in the D—50s and 60s group (96%, 91%, 91% versus 73%, 58%, 58%, respectively) ( P  = 0.020). Donor age was identified to be an independently significant risk factor for increased major complications ( P  = 0.007) and prognostic factor for reduced overall survival ( P  = 0.014). The optimal donor age cut off was determined to be 46.5 years old. Conclusion: Older donors are associated with poorer recipient outcomes after adult‐to‐adult LDLT. Usage of liver grafts from older donors should be carefully considered when choosing liver grafts for patients undergoing LDLT. Abstract : Older donors are associated with poorer recipient outcomes. Usage of liver grafts from older donors should be carefully considered when choosing liver grafts for patients undergoing LDLT.